Kandungan Fenolik, Flavonoid dan Aktivitas Antioksidan Ekstrak Daun Paku Laut (Acrostichum aureum L.) Fertil dan Steril di Kawasan Mangrove Kulon Progo, Yogyakarta - Naovi Nur Fadia Hanin; Rarastoeti Pratiwi (Journal of Tropical Biodiversity and Biotechnology, 2017)
Sea Fern (Acrostichum aureum L.), which typically grows in mangrove ecosystem, has two distinguished leaves which are fertile leaves (rich in spores) and sterile leaves (no spores). Those leaves are known rich in phenolic compounds. Flavonoids, moreover, which belong to class of phenolic compound, have antioxidant activity. This study aims were to analyze the phenolic content, flavonoid content, and antioxidant activity of fertile leaves, sterile leaves, and spores of sea fern which grow in mangrove ecosystem that is located in Kulon Progo, Yogyakarta. Leaf and spore samples were extracted using ethanol solvent. Then, total content of phenol and flavonoid were measured by spectrophotometry, while the antioxidant activity was measured by DPPH method. The results showed that the phenolic content of fertilized leaves and sterile leaves did not show a significant difference. In other hand, the spores sample showed highest both of flavonoids content (2.32 mg/mL) and the antioxidant activity with the IC50 value was 23.25 ppm. Thus, the ethanolic extracts of spores of sea fern sterile leaves showed the highest flavonoid content and could be categorized as a very strong antioxidant.